Konsepsi Musyawarah dalam Al-Qur'an: Analisis Fiqh Siyasah terhadap QS al-Naml/27: 29-35 - Bunyamin Bunyamin (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
Musyawarah (deliberation) is a negotiation by exchanging opinions from various parties on a matter to be considered and decided, in order to create a common good. The urgency of deliberation in human life is like taking honey from a beehive. Besides serving as a delicious drink, it also serves as a medicine. Implementation of musyawarah in the Qur'an encompasses all aspects of human activities, whether related to domestic life, religious affairs, or in the settlement of political affairs, inclusive tactics and war strategies. Among the benefits derived from the musyawarah is mutual respect for mutual decisions without accompanied by regret, although in the end the results of the decision do not produce maximum achievement.